Handbook of international relations (SAGE, 2013)
The original Handbook of International Relations was the first authoritative and comprehensive survey of the field of international relations. In this eagerly-awaited new edition, the editors have once again drawn together a team of the world's leading scholars of international relations to provide a state-of-the-art review and indispensable guide to the field, ensuring its position as the pre-eminent volume of its kind. A genuinely international undertaking, the handbook reviews the many historical, philosophical, analytical and normative roots to the discipline and the key contemporary topics of research and debate today